Kontribusi Promosi dalam Mempengaruhi Minat Kunjung Ulang Wisatawan ke Destinasi Wisata Bukit Langkisau - Nafia, Zitny Ilman; Suyuthie, Hijriyantomi (Departemen Pariwisata Universitas Negeri Padang, 2023)
This study intends to see the effect of promotion on tourist interest in repeat visits to Bukit Langkisau Tourism Destinations. This research uses quantitative methods with a causal associative approach. The data collection technique uses a questionnaire or questionnaire given to respondents or tourists who have visited the Bukit Langkisau Tourism Destination. Data analysis was assisted by using SPSS version 23.00 program assistance techniques, the estimated output was presented in tabular form. Based on the research that has been done, the following outputs are produced: (1) based on the character of the respondents, the majority of visitors are women aged 21-30 years, work as students, visit 2-5 times and the promotional media seen is social media. (2) based on variable data of interest in repeat visits obtained from 97 respondents, interest in repeat visits shows a good category with a percentage of 49.5% and promotion variables obtained from 97 respondents, promotions show a good category with a percentage of 45.4%. (3) Based on testing the hypothesis using the coefficient of determination test, an R square value of 0.619 is obtained. This explains that promotion has an influence of 69.1% on tourists' intention to return to Bukit Langkisau Tourism Destinations and 38.1% is influenced by other variables